Pengaruh Return On Equity (ROE), Debt To Assets Ratio (DAR), Price To Book Value (PBV) Dan Net Profit Margin (NPM) Terhadap Return Saham Perusahaan Sektor Perkebunan Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2017 - Ristyawan, Mochammad Ridwan (Fakultas Ekonomi dan Bisnis, UNTAN, 2019)
The financial condition of the plantation companies listed in the Indonesia Stock Exchange during 2011-2017 shows that the company has high asset value. The stock return of companies is experiencing a fluctuating condition. The sample in this study was taken using purposive sampling technique so that obtained 8 research samples. The data analysis tool used in this study is quantitative analysis. The results of the study are as follows: 1) Return on Equity (ROE) has significantly negatif effect on stock returns, 2) Debt to Assets Ratio (DAR) has not significantly positive effect on stock returns, 3) Price to Book Value (PBV) has significantly positive effect on stock returns, 4) Net Profit Margin (NPM) has not significantly positive effect on stock returns. In this study the ratio of PBV, and NPM proved to have no significant effect on stock returns, while ROE and DAR had a significant but opposite direction.